The Influence of Social Media Account X @Idextratime and Verbal Aggression on the Fanaticism of Manchester United Football Club Fans - Fadilah, Muhammad Rizki; Putri, Idola Perdini (PT FORMOSA CENDEKIA GLOBAL, 2024)
Social media, like Twitter, allows users to express opinions, comment, and share information freely. It has become a primary platform for fans to show support but also a space where verbal aggression can occur, influencing fan behavior and attitudes. This study examines the impact of the Twitter account @idextratime and verbal aggression on the fanaticism of Manchester United fans. Using a quantitative research method, a survey was conducted. Data analysis included descriptive analysis, classical assumption tests, multiple linear regression, and hypothesis testing (T-Test & F-Test).This research aims to determine how much influence each independent variable, namely social media and verbal aggression, has on the dependent variable, namely fanaticism, and how much influence the social media variable and verbal aggression simultaneously have on the fanaticism variable. Results showed significant influence, with social media and verbal aggression accounting for 88.4% of the variance in fanaticism. The study concluded that social media and verbal aggression significantly affect fan fanaticism.